High Confident Evaluation for Smart City Services - Sheng, Hao; Zhang, Yang; Wang, Wei; Shan, Zhiguang; Fang, Yufei; Lyu, Weifeng; Xiong, Zhang (Frontiers in Environmental Science, 2022)
This paper is about the evaluation and development of smart city services. Due to the great difference between cities, a single evaluation method cannot accurately describe the development of a city. In this paper, we classify cities by multiple labels according to various bases to give cities comprehensive description. Then, a Multi-level Service Evaluation System (MSES) is introduced. It considers individual weights to cities with different characteristics and evaluates the smart city services from different aspects. In addition to put forward the iterative development of smart city services, a Maturity Model based Service Evaluation (MMSE) framework is proposed based on the evaluation results of MSES. It constructs a standardized and high confident evaluation framework to analyze the current state of cities and make feedback to the government policies. Finally, we take 10 cities in China to demonstrate the effectiveness of MMSE during the development of smart city services.